2023
DOI: 10.1108/jmp-05-2022-0248
|View full text |Cite
|
Sign up to set email alerts
|

The influence of multitasking on creative work involvement: a conservation of resources perspective

Abstract: PurposeBased on conservation of resources theory, this study explored the relationship between multitasking and creative work involvement through the mediation of emotional exhaustion, taking regulatory focus as a first-stage moderator.Design/methodology/approachBased on a three-wave and two-source survey among a sample of 418 employees and 116 leaders, this study conducted multilevel analyses to examine the conceptual model.FindingsThe results showed that multitasking was negatively associated with creative w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 65 publications
0
0
0
Order By: Relevance
“…Scholars have also attempted to explain how organizational polychronicity is related to its consequences through COR theory. For example, Yang et al (2023) indicated that polychronicity consumes individuals' emotional resources and decreases their creativity. However, these studies have ignored the mediating role of time pressure, and most studies on time pressure have focused on its consequences (Prem et al, 2018;Song et al, 2023), especially on individual task performance (Prem et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Scholars have also attempted to explain how organizational polychronicity is related to its consequences through COR theory. For example, Yang et al (2023) indicated that polychronicity consumes individuals' emotional resources and decreases their creativity. However, these studies have ignored the mediating role of time pressure, and most studies on time pressure have focused on its consequences (Prem et al, 2018;Song et al, 2023), especially on individual task performance (Prem et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…First, we attempt to clarify the controversy between organizational polychronicity and individual performance (Wu et al, 2020), thereby responding to the call to explore how individual adaptive performance is generated (Park and Park, 2019) and how organizational polychronicity impacts individuals' performance (Wu et al, 2020;Franczak et al, 2024). Second, we examine time pressure as a mediator based on COR theory, thereby responding to calls for exploring the antecedents of time pressure (Eldor et al, 2017) and broadening the theoretical perspectives of organizational polychronicity research (Yang et al, 2023). Finally, we reveal important boundary conditions for the relationships between organizational polychronicity and its outcomes by identifying the moderating role of trait regulatory focus in the relationship between organizational polychronicity and time pressure, thereby contributing to the trait regulatory focus literature (Li et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations